Strategy theory and practice - Clegg, Stewart; Pitelis, Christos; Schweitzer, Jochen; Whittle, Andrea (SAGE Publications Ltd, 2023)
Written by an expert team and praised for its refreshing approach, this essential text offers a critical, holistic understanding of strategy theory and practice. The fourth edition has been fully updated to include: